Theoretical Calculation of System Performance of Fiber Optic Network with Chromatic Dispersion, Polarization Mode Dispersion, Polarization Dependent Loss, and Amplifier Spontaneous Emission Noise - Abuzariba, Suad Mohamed (University of Ottawa (Canada), 2010)
This thesis includes a theoretical study of the performance of an optical network system with linear impairments: chromatic dispersion (CD), polarization mode dispersion (PMD), polarization dependent loss (PDL), and amplified spontaneous emission (ASE) noise. Both the a-factor and bit error rate (BER) were used as performance parameters in this study. First, an analytical optical eye diagram evaluation for a system of highly mode coupled PMD/PDL fiber and lumped sections (up to fifteen sections) have been presented in this study. Based on this evaluation we found that with PDL considered as well as PMD, the a-factor of the output becomes higher than that of a Maxwellian fiber having the same total root mean-squared PMD and PDL values, when the mean-square PDL element of the lumped sections makes up the major portion of the total mean-square of the whole system. Whereas without considering PDL, the a-factor becomes higher as the mean-square PMD element of the Maxwellian fiber takes the major portion of the total mean-square PMD element of the whole system. Also the worst case for the a-factor occurred when the lumped sections were in the middle between two equivalent Maxwellian fibers, rether than if the lumped sections were followed by Maxwellian fiber or the Maxwellian fiber is followed by the lumped sections. We also note that two equivalent Maxwellian fibers connected in series will not give the same a-factor as a Maxwellian fiber equivalent calculated by concatenation rules unless they have the same values of PMD, PDL, and polarization direction correlation elements. Second, considering ASE-noise besides CD, PMD, and PDL, improved values of bit error rate (BER) were gotten using the moment generation function for the optical system in cases of ON-OFF modulation format and DPSK modulation format. We found that, even when considering the noise only without the signal, the probability density function of the output current was dependent on the output state of polarization.
Keywords: Physics, Optics.